PENENTUAN MODEL LANSKAP TEMPAT PEMBUANGAN SEMENTARA (TPS) DI KOTA ENDE BERBASIS SIG - Poke, Oskarfianus; Djoko, Riyanto; Nailufar, Balqis (Fakultas Pertanian, 2016)
Temporary disposal sites (TPS) are places that are used to accommodate garbage from the community. In general, the waste produced is followed up by storage, collection, transfer and processing. The existing landfill is still lacking and has not been in accordance with SNI standards. For this reason, this research was conducted by identifying and evaluating the location of the appropriate and optimal TPS location in the city of Ende. Data analysis uses GIS (Geographic Information System) and uses a survey method which includes observation and recording activities in the field. Based on the field survey and data processing obtained by the existing TPS there are 18 pieces. But currently there are 8 pieces left out of 18 which are still being used while the rest have been severely damaged. The results of data analysis using GIS, can find the appropriate location for the construction of TPS. For making landscape models (TPS) according to government standards and regulations No. 18 of 2010. In making TPS models, a waste management system and facilities are planned. Based on the results of using GIS, it can be concluded that there is no TPS landscape model and it is not yet appropriate in terms of the location and capacity of the volume of waste in Ende City. Tempat pembuangan sementara (TPS) adalah tempat yang digunakan untuk menampung sampah-sampah dari masyarakat. Secara umum sampah yang dihasilkan tersebut ditindak lanjuti dengan cara pewadahan, pengumpulan, pemindahan, dan pengolahan. Tempat pembuangan eksisting ternyata masih kurang dan belum sesuai standar SNI. Untuk itu penelitian ini dilakukan dengan cara mengidentifikasi dan mengevaluasi letak lokasi TPS yang sesuai dan optimal di Kota Ende. Analisis data menggunakan SIG (Sistem Informasi Geografis) dan menggunakan metode survei yang meliputi kegiatan pengamatan dan pencatatan di lapangan. Berdasarkan survey lapangan dan pengolahan data diperoleh TPS eksisting terdapat 18 buah. Tapi saat ini dari 18 buah tersisa 8 buah yang masih digunakan sedangkan sisanya telah rusak parah. Hasil anlisis data menggunakan SIG, dapat mengetahui lokasi yang sesuai untuk pembangunan TPS. Untuk pembuatan model lanskap (TPS) sesuai standar dan peraturan pemerintah No. 18 Tahun 2010. Dalam membuat model TPS, direncanakan sistem pengolahan sampah dan dilengkapi fasilitas. Berdasarkan hasil menggunakan SIG dapat di simpulkan bahwa belum adanya model lanskap TPS dan belum sesuai ditinjau dari penempatan lokasi dan daya tampung terhadap volume sampah di Kota Ende.